2022
DOI: 10.3389/fnbeh.2022.808590
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Sex-Dependent Changes in Locus Coeruleus Physiology and Anxiety-Like Behavior Following Acute Stressor Exposure

Abstract: Adolescence is a critical period of development with increased sensitivity toward psychological stressors. Many psychiatric conditions emerge during adolescence and animal studies have shown that that acute stress has long-term effects on hypothalamic-pituitary-adrenal axis function and behavior. We recently demonstrated that acute stress produces long-term electrophysiological changes in locus coeruleus and long-lasting anxiety-like behavior in adolescent male rats. Based on prior reports of increased stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…24 Later research delved into age-and sex-dependent variations in the physiology of LC neurons and anxiety-like behavior post-acute stressor exposure, but these studies maintained a within-group focus rather than comparing between groups. 25 Contrary to our observations, some research found no significant disparities in baseline action potential firing rates between sexes. However, upon injecting current into the neuron, F I G U R E 5 Differential protein expression and abundance in PC/SCP neurons from female and male mice.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…24 Later research delved into age-and sex-dependent variations in the physiology of LC neurons and anxiety-like behavior post-acute stressor exposure, but these studies maintained a within-group focus rather than comparing between groups. 25 Contrary to our observations, some research found no significant disparities in baseline action potential firing rates between sexes. However, upon injecting current into the neuron, F I G U R E 5 Differential protein expression and abundance in PC/SCP neurons from female and male mice.…”
Section: Discussioncontrasting
confidence: 99%
“…Pioneering research focusing on the membrane properties of LC neurons did not clarify the age and gender of the rats used in the experiments 24 . Later research delved into age‐ and sex‐dependent variations in the physiology of LC neurons and anxiety‐like behavior post‐acute stressor exposure, but these studies maintained a within‐group focus rather than comparing between groups 25 . Contrary to our observations, some research found no significant disparities in baseline action potential firing rates between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, what the proximate factor killing the females may be, tonic immobility may be a better option for a female than fighting her way out of the amplexus, as any movement in a large mating group automatically attracts attention of further nearby males and thus increases the probability of a mating ball formation. With these considerations in mind, it would be interesting to measure stress corticosterone levels in female R. temporaria and investigate how they correspond to age and sex ratio in breeding aggregations [45,48]. Future studies should consider investigating different frog densities, sex ratios and age classes, to test for mate choice and the potential costs associated with reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Located in the anterior pons, the locus coeruleus (LC), with its extensive innervations throughout the central nervous system, is the major noradrenergic nucleus of the brain and thereby controls a broad range of physiological processes that include cognition, learning and memory, sleep–wake cycle, arousal, attention, mood, anxiety and pain [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. These and other neurophysiological processes are known to be affected by changes in the discharge properties of LC neurons [ 7 ], which in turn are dependent on the intrinsic membrane properties and the ion channel constituents of these neurons.…”
Section: Introductionmentioning
confidence: 99%